2022
DOI: 10.1021/acsami.1c20088
|View full text |Cite
|
Sign up to set email alerts
|

Effectual Interface and Defect Engineering for Auger Recombination Suppression in Bright InP/ZnSeS/ZnS Quantum Dots

Abstract: The main issue in developing a quantum dot light-emitting diode (QLED) display lies in successfully replacing heavy metals with environmentally benign materials while maintaining high-quality device performance. Nonradiative Auger recombination is one of the major limiting factors of QLED performance and should ideally be suppressed. This study scrutinizes the effects of the shell structure and composition on photoluminescence (PL) properties of InP/ZnSeS/ZnS quantum dots (QDs) through ensemble and single-dot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…138 Another study found that this strain was associated with higher sulfur compositions, with lower sulfur composition gradients experiencing reduced strain, better suppressed Auger recombination, and decreased spectral diffusion. 139 Recent improvements in controlling the Zn chemistry of ZnSe/ZnS shellings, such as concomitant HF etching, increased shelling temperatures, and entropic ligand mixtures, have produced InP/ZnSe/ZnS QDs with near unity PLQYs and ensemble PL line widths as narrow as 35 nm 14,60,85,138 (Figure 7). In 2019, Won et al used HF etching concomitant with the initial ZnSe shell growth to remove oxides from the InP QD surface that impede initial shell deposition.…”
Section: Fluorescent Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…138 Another study found that this strain was associated with higher sulfur compositions, with lower sulfur composition gradients experiencing reduced strain, better suppressed Auger recombination, and decreased spectral diffusion. 139 Recent improvements in controlling the Zn chemistry of ZnSe/ZnS shellings, such as concomitant HF etching, increased shelling temperatures, and entropic ligand mixtures, have produced InP/ZnSe/ZnS QDs with near unity PLQYs and ensemble PL line widths as narrow as 35 nm 14,60,85,138 (Figure 7). In 2019, Won et al used HF etching concomitant with the initial ZnSe shell growth to remove oxides from the InP QD surface that impede initial shell deposition.…”
Section: Fluorescent Propertiesmentioning
confidence: 99%
“…This alloying can smooth the lattice change from ZnSe to ZnS to reduce lattice strain, but when compared directly, alloyed samples exhibit lower PLQYs than discrete ZnSe/ZnS shelled QDs. ,,, In 2019, Lee et al found that alloyed ZnSeS shells experienced more lattice strain than discrete ZnSe/ZnS shells, causing broader ensemble and single particle PL line widths . Another study found that this strain was associated with higher sulfur compositions, with lower sulfur composition gradients experiencing reduced strain, better suppressed Auger recombination, and decreased spectral diffusion …”
Section: Fluorescent Propertiesmentioning
confidence: 99%
“…Both oxidation defects and component doping could generate a large number of surface traps at the InP/ZnS interface, as these will cause energy losses, such as Förster resonance energy transfer (FRET) and Auger recombination (AR) [ 6 , 71 ]. To suppress the non-radiative progress, double-shell QDs were fabricated [ 72 ]. The conventional shell materials used in InP QDs are GaP, ZnS, ZnSe, and ZnSeS [ 6 , 73 , 74 , 75 , 76 ], as shown in Figure 5 .…”
Section: Influence Of Core/shell Structure On Performance Of Inp Qledsmentioning
confidence: 99%
“…Reproduced with permission. [ 148 ] Copyright 2021, American Chemical Society. g) Schematic representation of InP/ZnSeS/ZnS QDs with discrete and gradient shells and the negative trion in gradient shell.…”
Section: Blue‐emitting Inp‐based Qledsmentioning
confidence: 99%